ANALISIS REAKSI DAN TINGKAT PEMAHAMAN GEN Z TERHADAP WAYANG KULIT - Mohamad Andhika Tangguh Pradana; Chayara Evrillica; Jocelyn Sharon Givenia Hutagalung (CV. Denasya Smart Publisher, 2025)
This study examines Generation Z's understanding of Wayang Kulit amidst cultural transformation triggered by digitalization. Using a descriptive-quantitative approach with 60 respondents, this study analyzes three key components: cognitive understanding, affective responses, and cultural consumption behavior. Results indicate that while Gen Z possesses high awareness of Wayang Kulit, their understanding remains superficial, limited to popular characters and accessible narratives. Affectively, respondents demonstrated consistent cultural pride; however, this paradoxically contrasts with a low interest in watching traditional full-length performances. Behaviorally, exposure occurs primarily through short-form digital content, shifting Wayang's position from a moral education tool to merely visual art. Consequently, the study concludes that cultural preservation requires repackaging through digital storytelling and interactive formats to maintain Wayang Kulit's relevance in the future.